Depiction of musicians - Temples of India Project Team (Jio Institute, 2024)
There are many loose architectural fragments scattered within the Harshnath Temple Complex. In this fragment, musicians are depicted singing or playing a variety of musical instruments. At the centre is a male with long hair and a beard, playing the drum.